UNDERSTANDING THE ROLE OF PURCHASE INTENTION IN AFFECTING BUYING BEHAVIOR TOWARD GREEN PRODUCT FROM THE TPB PERSPECTIVE - Moh Farid Najib; Mutia Sari Dewi (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research explores how social media marketing strategies—guided by the Theory of Planned Behavior (TPB) and principles of Green Marketing—affect consumers' intentions and purchasing behaviors toward environmentally friendly products. With growing concerns about plastic waste, especially in densely populated and rapidly developing countries like Indonesia, this research aims to address the significant environmental challenges posed by high plastic consumption. This survey has been conducted toward 456 respondents. This study utilized nonprobability sampling by purposive sampling. Smart PLS 3 software used for structural equation modeling This approach allows for the collection of extensive data on consumer behavior and sentiments. The results reveal that Attitude, Subjective Norms, and Perceived Behavioral Control have a significant and positive impact on consumers' intentions to purchase eco-friendly products. Additionally, green advertising and eco-labeling play a crucial role in shaping actual buying behavior toward such products. The intention to purchase also significantly drives environmentally conscious buying behavior. However, green branding does not exhibit a positive influence on consumer purchasing decisions. This suggests that consumers are more likely to develop purchase intentions when companies effectively communicate their environmental commitment.